PELATIHAN PENGEMASAN DAN PENYULUHAN PEMBUATAN PUPUK KOMPOS: DESA PUSHARANG - Sucipto, Sucipto; Andriyanto, Teguh; Nadliroh, Kuni; Bhima P, Antowi; Indrajaya, Dimas; Mustofa, M. Ary (UNIVERSITAS PGRI MADIUN, 2019)
Abstract. Puhsarang Hamlet is a densely populated area. The majority of the work of the Puhsarang villagers work as farmers or farm laborers. Some communities, especially the younger generation who have just finished school, are still unemployed. The observation results show that there are business opportunities that can be offered by the local residents, namely livestock manure from residents, especially farmers. Most farmers have livestock. The animals that are owned are cows and goats. Waste of livestock manure can be optimized to be additional income to meet more needs for residents.Kata kunci : Waste, Fertilizer, Income Abstrak. Dusun Puhsarang merupakan kawasan wilayah yang padat peduduknya. Mayoritas pekerjaan masyarakat Desa Puhsarang bekerja sebagai petani ataupun buruh tani. Beberapa masyarakat khususnya generasi muda yang baru menyelesaikan sekolah masih menganggur. Hasil observasi terdapat peluang usaha yang bisa diberdaakan oleh warga sekitar yaitu kotoran ternak dari para warga terutama petani. Sebagian besar petani memiliki hewan ternak. Hewan ternak yang dimiliki yaitu sapi dan kambing. Limbah kotoran hewan ternak warga dapat dioptimalkan menjadi tambahan penghasilan untuk memenuhi kebutuhan yang lebih bagi warga.Keywords: Limbah, Pupuk, Penghasilan